Analysis Of Fraction Concepts Understanding In The Indonesian Realistic Mathematics Education (PMRI) Model : Students' Curiosity Perspective - GHOZALI, AKHMAD (Program Studi Pendidikan Matematika, Universitas Pancasakti Tegal, 2023)
This research was carried out using a mixed-method approach, combining qualitative and quantitative methods. The qualitative method was used to analyze the learning process conducted with the Indonesian realistic mathematics education (PMRI) model. Meanwhile, the quantitative method was used to measure the level of student curiosity and the impact of RME model on curiosity. The effectiveness of RME model was assessed by examining the teaching materials, which had been validated by an expert validator. The results indicated that the teaching materials were valid and suitable for the learning process. To evaluate the level of student curiosity, data collection was performed through questionnaire administration, which revealed that 64% of the students had a high level of curiosity. Furthermore, to determine the extent of PMRI model's impact on curiosity, a quantitative method was used, indicated that 2.5% of the fraction concepts understanding was influenced by student curiosity.